Does Abdominal Obesity Accelerate the Effect of Hypertriglyceridemia on Impaired Fasting Glucose? - Lee, Soojin (Yonsei University College of Medicine, 2010)
PURPOSE: This study sought to determine whether abdominal obesity is a risk factor for impaired fasting glucose (IFG) and hypertriglyceridemia and to verify whether moderate effect of abdominal obesity on the relationship between IFG and hypertriglyceridemia in Korea. MATERIALS AND METHODS: Data from the Korean National Health and Nutrition Examination Survey was used for the analysis. The study population included 5,938 subjects aged 20 year old drawn from non-diabetic participants in a health examination survey. The subjects were classified according to the presence of abdominal obesity based on waist circumference, IFG based on their fasting blood glucose level, and hypertriglyceridemia on their fasting triglyceride. RESULTS: The multivariate-adjusted odds ratios for the occurrence of hypertriglyceridemia were 2.91 in the abdominal obesity group as compared with the nonobesity group and 1.31 in subjects with IFG compared with the normoglycemia controls. Abdominal obesity was found to be positively moderated in the interaction between waist circumference and fasting blood sugar. CONCLUSION: The moderate effect between abdominal obesity and IFG contributes to the development of hypertriglyceridemia in Korea.